Transtracheal approach to repair of a tracheo‐colonic fistula 44 years after colonic interposition. Issue 11 (3rd April 2014) - Mehra, Saral; Scherl, Sophie; Lazarus, Cathy; Dewey, Eliza; Urken, Mark L.; Irish, Jonathan
ABSTRACT Background We present a case report of a trachea‐colonic fistula and demonstrate our unique approach to repair, which was efficient and effective. Methods The patient was a 50‐year‐old man who had a congenital tracheoesophageal fistula repair with colonic interposition as a child who now developed a fistula between his colon and trachea. Results We performed a transtracheal approach, with primary closure of redundant colon mucosa as well as direct repair of the trachea. An inferiorly based sternocleidomastoid muscle flap was interposed between these 2 layers to augment the repair. The patient had an uneventful recovery with an effective reconstitution of the alimentary tract and the airway. Conclusion Tracheo‐colonic fistula is an extremely rare pathology, and the scarring that develops after a prior esophagectomy makes a traditional lateral approach very difficult. The transtracheal approach is an effective method to obtain needed exposure in order to carry out the repair. © 2014 Wiley Periodicals, Inc. Head Neck 36: E117–E120, 2014